Izzy gets the f*ck across town [videorecording (DVD)] - Papierniak, Christian; Papierniak, Christian; Papierniak, Christian; Davis, Mackenzie; Davis, Mackenzie; Shawkat, Alia, 1989-; Osment, Haley Joel, 1988- (Shout! Factory, 2018)
A woman who is down on her luck must bike across Los Angeles to crash her ex-boyfriend's engagement party.